Universal Gestational Diabetes Screening and Antepartum Stillbirth Rates in Austria—A Population-Based Study. Issue 10 (October 2022) - Muin, Dana A.; Pfeifer, Bernhard; Helmer, Hanns; Oberaigner, Wilhelm; Leitner, Hermann; Kiss, Herbert; Neururer, Sabrina
Abstract : (Abstracted from Acta Obstet Gynecol Scand 2022;101:396–404) Approximately 1 in 6 pregnancies are affected by gestational diabetes mellitus (GDM), a risk factor for preeclampsia, fetal macrosomia, neonatal hypoglycemia, and antepartum stillbirth. The incidence of antepartum stillbirth is approximately 4/1000 births in high-income countries, and the risk of fetal death recurrence can be as high as 22-fold.